Consecutive 2-azidoallylation/click cycloaddition of active methylene for synthesis of functionalized hepta-1, 6-dienes with a bis-1, 2, 3-triazole scaffold. Issue 24 (9th November 2022) - Liu, Zhenhua; Chen, Huimin; Gan, Xingxing; Wang, Lianxiao; Lin, Ping; Li, Jiayi; Huang, Xiuxiu; Tian, Rongbiao; Liu, Xuan; Gao, Wen; Tang, Bo
Abstract : A tandem 2-azidoallylation/click cycloaddition reaction to access novel hepta-1, 6-diene skelecton can be successfully accomplished with methylene compounds, phenolic substituted vinyl azide and alkynes in one pot. Abstract : A tandem 2-azidoallylation/click cycloaddition reaction can be accomplished with methylene compounds, phenolic substituted vinyl azide and alkynes in one pot. This general cascade reaction smoothly enables the construction of novel multifunctional hepta-1, 6-dienes bearing quaternary/tertiary carbon and a bis-1, 2, 3-triazole scaffold in good to excellent yields.